Implantación de un sistema contable al local comercial Bianca del cantón Macará, provincia de Loja en el periodo febrero 2016 - Macas Palacios, María Belén (2017)
The completion of the thesis is justified as a prerequisite to the degree of Engineering in Accounting and Auditing; as well as to contribute to the progress of Bianca, since after organizing the company accounting the owner will have a better control in their cash and in each of the daily operations that appear in the business. In order to meet the stated objectives, we initially proceeded to sort and classify the source documentation, such as purchase and sale invoices. Then, the owner of the property, the rights and obligations elaborated the Initial Inventory, the memorandum of operations provided the basis for recording the entries in the Daily Book, General Ledger and other main books and auxiliaries until the Financial Statements are executed, with this information, the owner will make the best decisions for the aggrandizement of the business, control expenses and strengthen cash inflows. It is important to indicate that the development of the accounting process was carried out in accordance with the current Accounting Standards, concluding that the Accounting System is an optimal, efficient and effective tool when making decisions, investing, controlling expenses, control of the merchandise account among other aspects that guarantee the control of the business activities.